2017
DOI: 10.1002/2017jc012935
|View full text |Cite
|
Sign up to set email alerts
|

Bed failure induced by internal solitary waves

Abstract: The pressure field inside a porous bed induced by the passage of an Internal Solitary Wave (ISW) of depression is examined using high‐accuracy numerical simulations. The velocity and density fields are obtained by solving the Dubreil‐Jacotin‐Long Equation, for a two‐layer, continuously stratified water column. The total wave‐induced pressure across the surface of the bed is computed by vertically integrating for the hydrostatic and nonhydrostatic contributions. The bed is assumed to be a continuum composed of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 73 publications
(158 reference statements)
0
4
0
Order By: Relevance
“…Early research on the influence of ISW on seabed stability mainly combined with the two‐dimensional Biot consolidation theory to analyze how internal waves cause excessive pore water pressure on the seabed, and discussed the effects of different seabed and internal wave parameters on dynamic response (Williams & Jeng, 2007a, 2007b). Rivera Rosario et al (2017) found in their study on the permeability horizontal seabed model that the range of seabed damage is 2% of the depth of the low permeability seabed, and the gas‐bearing muddy seabed may experience instability within typical depths of the continental shelf. However, these studies are limited to quasi‐static Biot theory elastic models, thus failing to reflect accurately the accumulation of excess pore pressure caused by dynamic loads.…”
Section: Action Of Isw On the Seafloormentioning
confidence: 99%
“…Early research on the influence of ISW on seabed stability mainly combined with the two‐dimensional Biot consolidation theory to analyze how internal waves cause excessive pore water pressure on the seabed, and discussed the effects of different seabed and internal wave parameters on dynamic response (Williams & Jeng, 2007a, 2007b). Rivera Rosario et al (2017) found in their study on the permeability horizontal seabed model that the range of seabed damage is 2% of the depth of the low permeability seabed, and the gas‐bearing muddy seabed may experience instability within typical depths of the continental shelf. However, these studies are limited to quasi‐static Biot theory elastic models, thus failing to reflect accurately the accumulation of excess pore pressure caused by dynamic loads.…”
Section: Action Of Isw On the Seafloormentioning
confidence: 99%
“…On the one hand, the resuspension and transport of seafloor sediment induced by the shoaling ISWs can change the seafloor topography (McPhee-Shaw, 2006;Masunaga et al, 2016;Tian et al, 2021a). On the other hand, the strong shearing stress of the shoaling ISWs can lead to sand wave and even seabed failure (Ma et al, 2016;Rivera-Rosario et al, 2017;Tian et al, 2021b;Tian et al, 2022). Moreover, the propagation of the ISWs can lead to strong convergence and divergence of the sea surface or sudden strong currents in local seawater.…”
Section: Introductionmentioning
confidence: 99%
“…However, transient waves such as solitary waves and bores can be observed in coastal and ocean regions (Chanson 2009;Chan & Liu 2012;Pujara, Liu & Yeh 2015) and they can cause seabed failure (Packwood & Peregrine 1980;Liu, Park & Lara 2007;Young, Xiao & Maddux 2010;Sumer et al 2011;Jia et al 2019;Tehranirad, Kirby & Shi 2020), suggesting that transient wave-induced pore pressure and effective stresses, and their effects on instability within a deformable seabed, require attention as well. According to our literature survey, only a few studies have been carried out on this topic (Young et al 2009;Merxhani & Liang 2012;Rivera-Rosario, Diamessis & Jenkins 2017;Rivera-Rosario et al 2020) and they are typically numerical approaches. Moreover, the assumptions employed in the governing equations used in the numerical studies are not clearly stated, which demands further attention.…”
Section: Introductionmentioning
confidence: 99%